PROPOSAL FOR IMPLEMENTING UNDERGRADUATE COURSES IN SPEECH THERAPY AND OCCUPATIONAL THERAPY AT THE UNIVERSITY OF GURUPI (UNIRG): A RESPONSE TO SUPPRESSED DEMANDS AND REGIONAL DEVELOPMENT NEEDS - de Cirqueira, Jenilson Alves; Pereira, Thais Farias; de Alcântara, Angélica Alves; de Cirqueira, Jenilsa Alves; de Cirqueira, João Gabriel Barbosa (Seven Editora, 2025)
This article proposes the implementation of undergraduate programs in Speech-Language Pathology and Occupational Therapy at the University of Gurupi (UnirG), located in the municipality of Gurupi, Tocantins. Based on data from the 2022 Census, which indicate a growing pent-up demand for rehabilitation and inclusion services for neurodivergent individuals and individuals with psychomotor disabilities, coupled with the scarcity of programs in these areas in the North and Central-West regions of Brazil, the proposal is justified. The new legislation requiring the collection of data on disorders and neurodivergences reinforces this need. Gurupi, as a metropolitan hub and part of a government consortium in southern Tocantins, has sufficient infrastructure and demand, with the recently opened Monsenhor Geraldo Torres Specialized Rehabilitation Center (CER), inaugurated on June 3, 2025, serving as a catalyst. The potential for transferring resources from the Unified Health System (SUS) to Gurupi and the consortium municipalities is also analyzed, given the increased demand.DOI: https://doi.org/10.56238/sevened2025.029-081